Understanding the role of visual attention on wines' purchase intention: an eye-tracking study. Issue 2 (9th December 2019) - Monteiro, Patrícia; Guerreiro, João; Loureiro, Sandra Maria Correia
Abstract : Purpose: Wine bottles compete for consumers' attention in the shelf during the decisive moment of choice. This study aims to explore the role that visual attention to wine labels has on the purchase decision and the mediating role of quality perceptions and desire on such purchase behaviours. Wine awards and consumption situation are used as moderators.. Design/methodology/approach: The study was conducted in Portugal and 36 individuals participated in a 2 × 2 within subjects design (awarded/not awarded × self-consumption/social-consumption). For each scenario, individuals' attention, perceptions of quality, desire and purchase intentions were recorded. Findings: Data from eye-tracking shows that, during the purchase process, the amount of attention given to a bottle is determinant of individuals' purchase intentions, a relationship that increases in significance for bottles with awards and for when consumers are buying wine for a consumption situation involving a social environment. In addition, both quality perceptions and desire are confirmed to positively influence wines' purchase intentions. Originality/value: By using an eye monitoring method, this paper brings new insights into the wine industry by highlighting the impact that wines' labels and different consumption situations have on individuals' attention and purchase intention. Wine producers and retailers may benefit from the insights provided by the current study to refine their communication strategies by either highlighting product characteristics and pictorial elements, as it is the case of the awards, or communicating about their products for different consumption situations.